Cinema e educação: os professores, seus imaginários e suas relações com o audiovisual - Silva, Rozangela Martins da (2015)
This research is entitled: Cinema and Education: teachers, their imaginaries and relations with the visual audio. It is part of the post-graduation program at Universidade Federal de Santa Maria. This work investigates how cinema has been worked at Instituto Federal do Tocantins, Campus Araguaína. This investigation is theoretically based on scholars who study cinema, education, and social imaginary. They are Castoriadis (1982), Oliveira (2012); Duarte (2002), Fresquet (2013), Imbernon, Nóvoa (2009), Deleuze (1985) and Bergala (2008). This is a qualitative research. As a data generation, device semi-structured interviews were done with five teachers who teach students from the course of Computer Science Integrated to High School. One of our goals was to understand some possibilities of using cinema at school as a tool to empower teachers teaching practice. National cinema investigation also was inserted and highlighted here. Bardin s analyzes theory (1977) was used to analyze this data s research. Results point four relevant thematic area: cinema in the life, cinema at school, national cinema and knowledge and cinema. Teachers see cinema as a strong tool to produce knowledge and make it accessible to students in a certain way that only through the Seventh Art can do. However, some of them do not take much profit from cinema because they were not specifically prepared for that purpose. In this way, some get more profit than others do in how to explore this art s potential. National cinema is few known; consequently, it is not valued as much as it should. It is mentioned how cinema can help in the education and new generation formation can take profit from it. In overview, this work points a needing of offering opportunities where teachers can be exposed to different and specifically training aiming to empower to use cinema in their classes. The great majority of teachers did not have specific training to work with cinema, did not participate in symposia, conferences, forums on the topic. Thus, each seeking more, some less, go learning in everyday life, how to develop their practices involving the cinema. It appeared that the national cinema is little known and hence undervalued. It has also been seen in research that can be expanded using the cinema, from the potential of the seventh art in the formation of new generations. Thus, it is evident that this study is essential that made possible continuing education courses on the campus, which develops work, emphasizing the cinema as art, like creation, development of otherness, the expansion of the imaginary and knowledge. It is believed that from these activities are feasible the construction of knowledge also the cinematic bias is to enable you to (re) thinking of educational practices. Thus, we seek to see the film as a creative power and not just as an entertainment educational resource or content illustration.